THE NEW EXTRALEGAL CONCEPT OF LOBBYING REGULATION IN LITHUANIA: ALTERATIONS AND FUTURE GUIDELINES - Ambrasaitė, Monika (Politologija, 2016)
Republic of Lithuania Law on Lobbying Activities (further – LLA) extralegal concept is considered to be deficient, regulation – ineffective. In this context, on January 23rd, 2015 Draft Law on Amendment of Republic of Lithuania Law on Lobbying Activities (further – DLALLA) was introduced. Functional blocks of legal rules from which legal regulation of lobbying consists and whether the regulation properly correlates with the reality of lobbying processes depend on the extralegal concept of regulation. In the context of theory and practice of lobbying it is investigated how fundamental elements of the concept of lobbying – essence of the phenomenon, subjects, target and methods – are disclosed in the DLALLA, qualitative alteration of the DLALLA is estimated while comparing it with the LLA, recommendations for improving the draft law based on the latter analysis are provided. Analysis of the issue of lobbying essence revealed frailty of the extralegal concept of the DLALLA. After moving from “actions aimed to influence” to “actions that influence” the scope of the regulation of lobbying is being unreasonably reduced. Taking into account the purpose of the regulation of lobbying two possibilities should be considered – returning to a conceptual minimum of lobbying defined in the LLA or, in order to avoid unreasonable expansion of regulation, determining lobbying through lobbying contact. Target of lobbying by the content in both LLA and DLALLA is identified identically, differing only in phrasing. Taking into consideration that current regulation of lobbying in Lithuania is inactive, target area of lobbying should have been reformed while modeling extralegal concept of the DLALLA. One of possible alternatives is to narrow target area of lobbying by purifying which subjects of public authorities constitute priority and defining that lobbying activities are regulated only in respect of these subjects. Expansion of lobbying subjects in the DLALLA up to three lobbying categories is one of the most successful moments of the extralegal concept of the DLALLA. Latter reveals that while reforming legal regulation the theory of lobbying can be taken into account, situation of lobbying processes in the country can be evaluated and the most optimum version can be selected. Adopting DLALLA would lead to a significant influence in the amount of information about lobbying activities.While comparing lobbying methods in the DLALLA and LLA no alterations were identified which is estimated as a negative aspect. In the present case it should be analyzed and evaluated which methods of indirect lobbying are most effective and prevalent in Lithuanian and, depending on these methods, additional legal regulations should be created. In order to achieve a higher level of transparency in the process of lobbying a possibility to spread the regulation of lobbying in such formalized and well known areas of impact on public authority as right of petition, right to criticize the work of state institutions and officers, right to convene in legislative initiative, etc., should be considered.